Clasmatodendrosis is associated with dendritic spines and does not represent autophagic astrocyte death in influenza-associated encephalopathy - Tachibana, Masaya; Mohri, Ikuko; Hirata, Ikuko; Kuwada, Ayano; Kimura-Ohba, Shihoko; Kagitani-Shimono, Kuriko; Fushimi, Hiroaki; Inoue, Takeshi; Shiomi, Masashi; Kakuta, Yukio; Takeuchi, Makoto; Murayama, Shigeo; et al. (Brain & development (Tokyo. 1979), 2019)
Influenza-associated encephalopathy (IAE) is one of the most serious CNS complications of an influenza virus infection, with unclear pathophysiology. Clasmatodendrosis is a complex of morphological changes in astrocytes characterized by fragmentation of the distal processes and swollen cell bodies. Although pathologists in Japan have long been aware of the presence of clasmatodendrosis in IAE brains, no details of the phenomenon have been published to date. We aimed to confirm the existence, and characterize the spatial distribution of clasmatodendrosis in postmortem IAE brains. Autopsied brains from 7 patients with IAE and 8 non-IAE subjects were examined immunohistochemically. In addition, immunofluorescent staining and electron microscopy were performed. Clasmatodendrosis was present in all examined regions of the IAE brains, but none of the control brains. Fragmented processes of astrocytes in IAE brains were closely adjacent to synapses on the dendritic spines, with the fragmentation especially prominent in the cerebellar molecular layer. In addition, the clasmatodendrotic astrocytes were negative for autophagy markers. Furthermore, whereas aquaporin 4 was predominantly detected in the perivascular endfeet of astrocytes in the control brains, its primary localization site shifted to the fragmented perisynaptic processes in the IAE brains. Clasmatodendrosis was distributed diffusely in the IAE brains in close association with synapses, and was not caused by astrocyte autophagy. Clasmatodendrosis may be a suggestive pathological feature of IAE.